Mechanical properties of load-bearing biological materials - Qwamizadeh, Mahan (Nanyang Technological University, 2017)
Bone, a typical load-bearing biological material, composed of ordinary base materials such as organic protein and inorganic mineral arranged in a hierarchical architecture, exhibits extraordinary mechanical properties. Up to now, most of previous studies focused on its mechanical properties under static loading. However, failure of the bone occurs often under dynamical loading. One of the key functions of load-bearing biological materials, is to protect their inside fragile organs by effectively damping dynamic impact. How those materials achieve this remarkable function remains largely unknown. An interesting question is: Are the structural sizes and layouts of the bone related or even adapted to the functionalities demanded by its dynamic performance? In this thesis, systematic finite element analysis was performed on the dynamic response of nanoscale bone structures under dynamic loading. It was found that for a fixed mineral volume fraction and unit cell area, there exists a nanoscale staggered structure at some specific feature size and layout that exhibits the fastest attenuation of stress waves. Remarkably, these specific feature sizes and layouts are in excellent agreement with those at experimentally observed in the bone at the same scale, indicating that the structural size and layout of the bone at the nanoscale are evolutionarily adapted to its dynamic behavior. Furthermore, This study shows that the nanostructure of bone very well synergizes the two mechanisms to achieve the fast stress wave attenuation which are stress wave scattering due to the protein-mineral interfaces and kinetic energy dissipation due to the viscosity of biopolymer components. Moreover, considering a self-similar hierarchical model, a theoretical approach was established to investigate the damping behavior of load-bearing biological materials in relation to the biopolymer viscous characteristics, the loading frequency, and the geometrical parameters of mineral inclusions as well as the hierarchy number. It was found that the damping properties of biological materials are greatly tuned and enhanced by the staggered and hierarchical organization of the organic and inorganic constituents. Finally, a theoretical framework was developed to establish the elastic bounds for the storage and loss moduli of various bioinspired staggered composites such as regular staggering, regular staggering with an offset, stairwise, herringbone and random staggering architectures. In a recursive way, the elastic bounds were further extended for bioinspired composites with multiple levels of structural hierarchy, and the effect of structural hierarchy was investigated; a theoretical approach was developed to estimate the damping properties of the hierarchical biocomposite at different length scales. It was found that, in comparison with other structural architectures, stairwise staggering structure generally gives higher loss viscoelasticity. The present work points out the importance of dynamic effect on the biological evolution of load-bearing biological materials.